Preparation method of foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol
By loading poly3-amino/3-amidethiophene and graphyne/tungsten trioxide nanoparticles on the nickel foam surface, a foam nickel foam composite material with excellent degradation rate and repeat stability is prepared, which solves the problem of insufficient stability and degradation rate of existing photocatalytic materials when treating wastewater containing paranitrophene.
Patent Information
- Application Number
- CN202411418670.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-12
AI Technical Summary
When existing photocatalytic materials treat paranitrophene-containing wastewater, their stability and reusability are insufficient, and the degradation rate needs to be improved, which limits industrial applications.
A composite photocatalytic degradation material is formed by loading poly3-amino/3-amidethiophene and graphyne/tungsten trioxide nanoparticles on the surface of the foam.
The ultraviolet and visible light degradation rate of paranitrophenol is improved, and the repetitive stability performance of photocatalytic degradation is significantly improved.
Smart Images

Figure CN119500261B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalytic degradation materials for sewage treatment, in particular to a method for preparing a foamed nickel-based composite material for photocatalytically degrading p-nitrophenol. Background Art
[0002] Para-nitrophenol is a key chemical organic compound, widely used in the dye industry, chemical and rubber synthesis, gunpowder manufacturing and other fields. However, it is also the main organic pollutant in industrial wastewater, with biological toxicity, carcinogenicity, teratogenicity, and difficult to biodegrade, posing a serious threat to human health and the ecological environment. At present, the methods for treating wastewater containing para-nitrophenol mainly include extraction, physical adsorption and membrane separation technology. The extraction method has low treatment efficiency and requires chemical reagents; the adsorption material of the physical adsorption method is not easy to reuse and requires frequent regeneration; membrane separation technology is limited by high cost and complex equipment.
[0003] Photocatalytic degradation technology provides a green and environmentally friendly solution to the problem of treating wastewater containing p-nitrophenol. Photocatalytic materials generate photogenerated electron-hole pairs under light, which in turn generate strong oxidizing active free radicals to oxidatively degrade organic pollutants. This process does not require additional chemical reagents and complex equipment, and is an ideal direction for treating wastewater containing p-nitrophenol. However, in the prior art, the stability and reusability of related photocatalytic materials still need to be improved, and the degradation rate of p-nitrophenol under ultraviolet-visible light also needs to be further improved. The solution to these problems is crucial for the industrial photodegradation treatment of wastewater containing p-nitrophenol. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol. The foamed nickel-based composite material prepared by the method has excellent degradation rates of p-nitrophenol under ultraviolet and visible light and outstanding repeated stability of p-nitrophenol photocatalytic degradation.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] The present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0007] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene;
[0008] Step [2] Synthesis of graphyne / tungsten trioxide nanoparticles;
[0009] Step [3]: Loading poly 3-amino / 3-amidethiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate to finally obtain the nickel foam-based composite material.
[0010] Preferably, the step [1] specifically includes the following operations:
[0011] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol and mixed to form a base solution A; L-proline was added to deionized water and mixed to form an additive solution A; a certain amount of additive solution A was added to the base solution A, and the reaction was carried out at room temperature for 3-5 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0012] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide are added to ethanol and mixed to form a base solution B; L-pyroglutamic acid is added to deionized water and mixed to form an additive solution B; a certain amount of additive solution B is added to the base solution B, and the reaction is carried out at room temperature for 2-3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0013] Preferably, in step a1, the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid A is 150-240 mL, and the amount of hexamethylenediamine added is 80-150 g; the concentration of L-proline in the additive liquid A is 90 g / L-130 g / L; and the volume ratio between the additive liquid A and the base liquid A is 1-3:4-7.
[0014] Preferably, in step a2, the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid B is 130-180 mL, and the amount of acrylamide added is 100-120 g; the concentration of L-pyroglutamic acid in the additive liquid B is 50 g / L-80 g / L; and the volume ratio between the additive liquid B and the base liquid B is 1-2:3-5.
[0015] Preferably, the step [2] specifically includes the following operations:
[0016] b1. Add phosphotungstic acid and cinchoninic acid to ethanol and mix to form an additive solution C; add sodium tungstate, ammonium chloride and graphyne nanoparticles to deionized water and mix to form a base solution C; add a certain amount of additive solution C to the base solution C to form a synthetic solution, put the synthetic solution into a reactor, heat to 60-80°C for reaction for 4-6 hours, and filter to obtain a solid phase graphyne / tungsten trioxide nanoparticle precursor;
[0017] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 200°C-250°C for 1 to 2 hours to obtain the Graphene / tungsten trioxide nanoparticles.
[0018] Preferably, in step b1, the amount of phosphotungstic acid added to each liter of the additive liquid C is 200-240 g, and the amount of cinchonine added is 30-50 g; the concentration of sodium tungstate in the base liquid C is 160 g / L-190 g / L, the concentration of ammonium chloride is 50 g / L-90 g / L, and the concentration of graphyne nanoparticles is 230 g / L-250 g / L; the volume ratio between the additive liquid C and the base liquid C in the synthetic liquid is 1-3:3-5.
[0019] Preferably, the step [3] specifically includes the following operations:
[0020] c1. adding dicobalt octacarbonyl and the graphyne / tungsten trioxide nanoparticles to dimethyl sulfoxide to form a loading promotion solution;
[0021] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a certain proportion to form a mixed solution, the metal nickel foam is immersed in the mixed solution, and the mixture is immersed at room temperature for 10-30 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred, and the mixture is reacted at room temperature for 3-4 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material.
[0022] Preferably, in step c1, the amount of graphyne / tungsten trioxide nanoparticles added in each liter of the promoting solution is 170-210 g, and the amount of dicobalt octacarbonyl added is 40-70 g.
[0023] Preferably, in step c2, the volume ratio of the 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution in the mixed solution is 1:1; the weight of the nickel foam immersed in each liter of the mixed solution is 130-170 g; and the volume ratio between the load-promoting liquid and the mixed solution is 1:1.
[0024] Positive effects of the present invention: The nickel-based foam composite material prepared according to the method of the present invention is a composite photocatalytic degradation material formed by further wrapping graphyne / tungsten trioxide nanoparticles with poly-3-amino / 3-amidethiophene organic matter on the surface of nickel foam by condensation polymerization of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidethiophene. The performance characteristics are as follows: the conjugation of the thiophene ring in the poly 3-amino / 3-amidothiophene organic matter is conducive to electron migration, the polar amino group and amide group can form hydrogen bonds with water, which is conducive to the hydrophilicity of the foam nickel composite material, and the amino group and amide group are electron-donating groups, which can increase the electron cloud density of the connected atoms and enhance the adsorption capacity of the nitrophenol; the nanocomposite particles formed by graphyne and tungsten trioxide are conducive to the separation efficiency of photogenerated electron holes, and at the same time, the smaller band gap width and wider spectral response of the poly 3-amino / 3-amidothiophene and the visible light catalytic characteristics of the n-type semiconductor tungsten trioxide work synergistically to improve the efficiency of the composite material in absorbing visible light and ultraviolet light to generate photogenerated electron holes, thereby causing the production of strong oxidizing free radicals and effectively improving the degradation rate of nitrophenol.
[0025] In conclusion, the nickel-based foam composite material prepared according to the present invention has excellent degradation rates of p-nitrophenol under ultraviolet and visible light and outstanding repeated stability of p-nitrophenol photocatalytic degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the preparation process of the foamed nickel-based composite material of the present invention;
[0027] Figure 2 is a schematic structural diagram of the foamed nickel-based composite material of the present invention;
[0028] Figure 3 is the p-nitrophenol photocatalytic degradation rate of the simulated p-nitrophenol-containing wastewater treated in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0029] Figure 4 It is a relationship diagram between the number of times of using Example 1, Comparative Example 1 and Comparative Example 2 of the present invention to treat simulated p-nitrophenol-containing wastewater and the photocatalytic degradation rate of p-nitrophenol. DETAILED DESCRIPTION
[0030] Reference Figure 1 The present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0031] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0032] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine are added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution A is 150-240 mL, and the amount of hexamethylenediamine added is 80-150 g), and the mixture is mixed to form a base solution A; L-proline is added to deionized water to form an additive solution A having an L-proline concentration of 90 g / L-130 g / L; a certain amount of additive solution A is added to the base solution A (the volume ratio between the additive solution A and the base solution A is 1 to 3:4 to 7), and the mixture is reacted at room temperature for 3 to 5 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0033] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide are added to ethanol and mixed to form a base liquid B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid B is 130-180 mL, and the amount of acrylamide added is 100-120 g); L-pyroglutamic acid is added to deionized water and mixed to form an additive liquid B with an L-pyroglutamic acid concentration of 50 g / L-80 g / L; a certain amount of additive liquid B is added to the base liquid B (the volume ratio between the additive liquid B and the base liquid B is 1-2:3-5), and the reaction is carried out at room temperature for 2-3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0034] Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations:
[0035] b1. Add phosphotungstic acid and cinchonine to ethanol and mix to form an additive solution C (the amount of phosphotungstic acid added to each liter of the additive solution C is 200-240g, and the amount of cinchonine added is 30-50g); sodium tungstate, ammonium chloride and graphyne nanoparticles are added to deionized water and mixed to form a base solution C with a sodium tungstate concentration of 160g / L-190g / L, an ammonium chloride concentration of 50g / L-90g / L, and a graphyne nanoparticle concentration of 230g / L-250g / L; a certain amount of additive solution C is added to the base solution C to form a synthetic solution (the volume ratio between the additive solution C and the base solution C is 1-3:3-5), the synthetic solution is placed in a reactor, heated to 60-80°C for reaction for 4-6 hours, and filtered to obtain a solid-phase graphyne / tungsten trioxide nanoparticle precursor;
[0036] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 200°C-250°C for 1 to 2 hours to obtain the Graphene / tungsten trioxide nanoparticles.
[0037] Step [3] loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate specifically comprises the following operations:
[0038] c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphyne / tungsten trioxide nanoparticles added per liter of the promotion solution is 170-210g, and the amount of octacarbonyl dicobalt added is 40-70g;
[0039] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal nickel foam is immersed in the mixed solution (the weight of the nickel foam immersed in each liter of the mixed solution is 130-170g), and the mixture is immersed at room temperature for 10-30 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 3-4 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material, and its microstructure is shown in the figure below Figure 2 shown.
[0040] The preferred embodiments of the present invention are described below by way of example.
[0041] Example 1
[0042] Preferred embodiment 1 of the present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0043] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0044] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added per liter of the base solution A was 230 mL, and the amount of hexamethylenediamine added was 140 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 120 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 3:5), and the mixture was reacted at room temperature for 5 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0045] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution B was 170 mL and the amount of acrylamide added was 110 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B with an L-pyroglutamic acid concentration of 70 g / L; a certain amount of additive solution B was added to the base solution B (the volume ratio between the additive solution B and the base solution B was 2:5), and the reaction was carried out at room temperature for 3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0046] Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations:
[0047] b1. Add phosphotungstic acid and cinchonine to ethanol and mix to form an additive solution C (the amount of phosphotungstic acid added to each liter of the additive solution C is 230g, and the amount of cinchonine added is 40g); sodium tungstate, ammonium chloride and graphyne nanoparticles are added to deionized water and mixed to form a base solution C with a sodium tungstate concentration of 180g / L, an ammonium chloride concentration of 80g / L, and a graphyne nanoparticle concentration of 240g / L; a certain amount of additive solution C is added to the base solution C to form a synthetic solution (the volume ratio between the additive solution C and the base solution C is 3:4), the synthetic solution is placed in a reactor, heated to 70°C for reaction for 5 hours, and filtered to obtain a solid-phase graphyne / tungsten trioxide nanoparticle precursor;
[0048] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 230° C. for 2 hours to obtain the Graphene / tungsten trioxide nanoparticles.
[0049] Step [3] loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate specifically comprises the following operations:
[0050] c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphyne / tungsten trioxide nanoparticles added per liter of the promotion solution is 180g and the amount of octacarbonyl dicobalt added is 65g;
[0051] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal nickel foam is immersed in the mixed solution (the weight of the nickel foam immersed in each liter of the mixed solution is 160 g), and immersed at room temperature for 10-30 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 3.5 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material, recorded as Example 1.
[0052] Comparative Example 1
[0053] This comparative example 1 provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0054] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0055] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution A was 170 mL and the amount of hexamethylenediamine added was 90 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 100 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 2:5), and the mixture was reacted at room temperature for 4 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0056] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution B was 140 mL and the amount of acrylamide added was 110 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B with an L-pyroglutamic acid concentration of 60 g / L; a certain amount of additive solution B was added to the base solution B (the volume ratio between the additive solution B and the base solution B was 2:3), and the reaction was carried out at room temperature for 2 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0057] Step [2] loading poly 3-amino / 3-amidothiophene and graphyne nanomaterials on the surface of the nickel foam substrate specifically comprises the following operations:
[0058] c1. The octacarbonyl dicobalt and graphene were added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphene added to the promotion solution was 180 g and the amount of octacarbonyl dicobalt added was 60 g per liter;
[0059] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal nickel foam is immersed in the mixed solution (the weight of the nickel foam immersed in each liter of the mixed solution is 150 g), and immersed at room temperature for 20 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 3-4 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / nanomaterial loaded on the surface, which is the nickel foam-based composite material, recorded as Comparative Example 1.
[0060] Comparative Example 2
[0061] This comparative example 2 provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0062] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0063] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added per liter of the base solution A was 200 mL, and the amount of hexamethylenediamine added was 140 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 110 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 3:5), and the mixture was reacted at room temperature for 4 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0064] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base liquid B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid B was 170 mL and the amount of acrylamide added was 105 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive liquid B with an L-pyroglutamic acid concentration of 60 g / L; a certain amount of additive liquid B was added to the base liquid B (the volume ratio between the additive liquid B and the base liquid B was 2:5), and the reaction was carried out at room temperature for 3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0065] Step [2] loading poly 3-amino / 3-amidothiophene and tungsten trioxide nanoparticles on the surface of the nickel foam substrate, specifically comprising the following operations:
[0066] c1. The octacarbonyl dicobalt and tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of tungsten trioxide nanoparticles added per liter of the promotion solution is 200 g, and the amount of octacarbonyl dicobalt added is 60 g;
[0067] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal foam nickel is immersed in the mixed solution (the weight of the foam nickel immersed in each liter of the mixed solution is 160 g), and immersed at room temperature for 20 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 4 hours to obtain a foam nickel with poly 3-amino / 3-amidethiophene and tungsten trioxide nanoparticles loaded on the surface, which is the foam nickel-based composite material, recorded as Comparative Example 2.
[0068] In order to analyze the photocatalytic degradation removal rate of p-nitrophenol in the treatment of p-nitrophenol-containing wastewater in Example 1, Comparative Example 1 and Comparative Example 2, p-nitrophenol was added to deionized water to prepare simulated p-nitrophenol wastewater with a p-nitrophenol concentration of 200 mg / L. 100 ml of simulated p-nitrophenol wastewater was poured into beakers respectively, and 25 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed into beakers respectively. A xenon lamp light source was used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for 14 hours under the conditions of working current 15A and working voltage 14V, and ultraviolet light (λ=380nm) and visible light (λ=500nm) were used to treat the corresponding simulated p-nitrophenol wastewater with photocatalytic degradation. The photocatalytic degradation rate of p-nitrophenol in the simulated p-nitrophenol wastewater after 4 hours of photocatalytic degradation was measured using an ultraviolet-visible spectrophotometer, and the results are as follows: Figure 3 As shown, the photocatalytic degradation rates of p-nitrophenol under ultraviolet light and visible light in Example 1 are 91% and 83%, respectively, while the photocatalytic degradation rates of p-nitrophenol under ultraviolet light and visible light in Comparative Example 1 and Comparative Example 2 can only reach 25%, 17% and 41%, 23%, respectively.
[0069] In addition, in order to analyze the repeated use stability of Example 1, Comparative Example 1 and Comparative Example 2, the relationship between the number of uses of Example 1, Comparative Example 1 and Comparative Example 2 and the photocatalytic degradation rate of p-nitrophenol under the above-mentioned treatment conditions is as follows: Figure 4 As shown by Figure 4It can be seen that the photocatalytic degradation rate of p-nitrophenol in Example 1 after the sixth repeated treatment of 100 ml of simulated p-nitrophenol wastewater under ultraviolet light and visible light for 4 hours can still reach 87% and 80%; the photocatalytic degradation rate of p-nitrophenol in Comparative Examples 1 and 2 after the sixth repeated treatment of 100 ml of simulated p-nitrophenol wastewater under ultraviolet light and visible light for 4 hours is significantly reduced, especially Comparative Example 1 has no catalytic properties.
[0070] In summary, the nickel-based composite material prepared according to the present invention has excellent ultraviolet and visible light degradation rates of p-nitrophenol and outstanding photocatalytic degradation and repeated use stability of p-nitrophenol.
[0071] To illustrate in further detail, three additional examples are provided below.
[0072] Example 2
[0073] Preferred embodiment 2 of the present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0074] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0075] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution A was 150 mL and the amount of hexamethylenediamine added was 80 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 130 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 1:4), and the mixture was reacted at room temperature for 3 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0076] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution B was 130 mL and the amount of acrylamide added was 120 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B with an L-pyroglutamic acid concentration of 50 g / L; a certain amount of additive solution B was added to the base solution B (the volume ratio between the additive solution B and the base solution B was 1:3), and the reaction was carried out at room temperature for 2 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0077] Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations:
[0078] b1. Add phosphotungstic acid and cinchonine to ethanol and mix to form an additive solution C (the amount of phosphotungstic acid added to each liter of the additive solution C is 240g, and the amount of cinchonine added is 30g); sodium tungstate, ammonium chloride and graphyne nanoparticles are added to deionized water and mixed to form a base solution C with a sodium tungstate concentration of 190g / L, an ammonium chloride concentration of 50g / L, and a graphyne nanoparticle concentration of 230g / L; a certain amount of additive solution C is added to the base solution C to form a synthetic solution (the volume ratio between the additive solution C and the base solution C is 1:3), the synthetic solution is placed in a reactor, heated to 80°C for reaction for 4 hours, and filtered to obtain a solid-phase graphyne / tungsten trioxide nanoparticle precursor;
[0079] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 200° C. for 2 hours to obtain the Graphene / tungsten trioxide nanoparticles.
[0080] Step [3] loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate specifically comprises the following operations:
[0081] c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphyne / tungsten trioxide nanoparticles added per liter of the promotion solution is 210g and the amount of octacarbonyl dicobalt added is 40g;
[0082] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal nickel foam is immersed in the mixed solution (the weight of the nickel foam immersed in each liter of the mixed solution is 170 g), and immersed at room temperature for 30 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 3 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material.
[0083] Example 3
[0084] Preferred embodiment 3 of the present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0085] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0086] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution A was 240 mL, and the amount of hexamethylenediamine added was 150 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 90 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 3:7), and the mixture was reacted at room temperature for 5 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0087] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution B was 180 mL and the amount of acrylamide added was 100 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B with an L-pyroglutamic acid concentration of 80 g / L; a certain amount of additive solution B was added to the base solution B (the volume ratio between the additive solution B and the base solution B was 2:5), and the reaction was carried out at room temperature for 3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0088] Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations:
[0089] b1. Add phosphotungstic acid and cinchonine to ethanol and mix to form an additive solution C (the amount of phosphotungstic acid added to each liter of the additive solution C is 200g, and the amount of cinchonine added is 50g); sodium tungstate, ammonium chloride and graphyne nanoparticles are added to deionized water and mixed to form a base solution C with a sodium tungstate concentration of 160g / L, an ammonium chloride concentration of 90g / L, and a graphyne nanoparticle concentration of 250g / L; a certain amount of additive solution C is added to the base solution C to form a synthetic solution (the volume ratio between the additive solution C and the base solution C is 3:5), the synthetic solution is placed in a reactor, heated to 60°C for reaction for 6 hours, and filtered to obtain a solid-phase graphyne / tungsten trioxide nanoparticle precursor;
[0090] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 250° C. for 1 hour to obtain the Graphene / tungsten trioxide nanoparticles.
[0091] Step [3] loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate specifically comprises the following operations:
[0092] c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphyne / tungsten trioxide nanoparticles added per liter of the promotion solution is 170g and the amount of octacarbonyl dicobalt added is 70g;
[0093] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal foam nickel is immersed in the mixed solution (the weight of the foam nickel immersed in each liter of the mixed solution is 130 g), and immersed at room temperature for 10 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the reaction is carried out at room temperature for 4 hours to obtain a foam nickel with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the foam nickel-based composite material.
[0094] Example 4
[0095] Preferred embodiment 4 of the present invention provides a method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, comprising the following steps performed in sequence:
[0096] Step [1] Preparation of 2,5-dibromo-3-aminothiophene and 2,5-dibromo-3-amidothiophene, specifically comprising the following operations:
[0097] a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol (the amount of 2,5-dibromo-3-hexylthiophene added per liter of the base solution A was 195 mL and the amount of hexamethylenediamine added was 115 g), and the mixture was mixed to form a base solution A; L-proline was added to deionized water to form an additive solution A having an L-proline concentration of 110 g / L; a certain amount of additive solution A was added to the base solution A (the volume ratio between the additive solution A and the base solution A was 2:5), and the mixture was reacted at room temperature for 4 hours to obtain a 2,5-dibromo-3-aminothiophene product solution;
[0098] a2. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B (the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base solution B was 155 mL and the amount of acrylamide added was 110 g); L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B with an L-pyroglutamic acid concentration of 65 g / L; a certain amount of additive solution B was added to the base solution B (the volume ratio between the additive solution B and the base solution B was 1:4, and the reaction was carried out at room temperature for 2.5 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
[0099] Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations:
[0100] b1. Add phosphotungstic acid and cinchonine to ethanol and mix to form an additive solution C (the amount of phosphotungstic acid added to each liter of the additive solution C is 220g, and the amount of cinchonine added is 40g); sodium tungstate, ammonium chloride and graphyne nanoparticles are added to deionized water and mixed to form a base solution C with a sodium tungstate concentration of 175g / L, an ammonium chloride concentration of 70g / L, and a graphyne nanoparticle concentration of 240g / L; a certain amount of additive solution C is added to the base solution C to form a synthetic solution (the volume ratio between the additive solution C and the base solution C is 2:4), the synthetic solution is placed in a reactor, heated to 70°C for reaction for 5 hours, and filtered to obtain a solid-phase graphyne / tungsten trioxide nanoparticle precursor;
[0101] b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 230° C. for 1.5 hours to obtain the Graphene / tungsten trioxide nanoparticles.
[0102] Step [3] loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate specifically comprises the following operations:
[0103] c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution, wherein the amount of graphyne / tungsten trioxide nanoparticles added per liter of the promotion solution is 190g, and the amount of octacarbonyl dicobalt added is 55g;
[0104] c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a volume ratio of 1:1 to form a mixed solution, and the metal nickel foam is immersed in the mixed solution (the weight of the nickel foam immersed in each liter of the mixed solution is 150 g), and the mixture is immersed at room temperature for 20 minutes. Then, a certain amount of the loading promotion liquid is added to the mixed solution and stirred sufficiently (the volume ratio between the loading promotion liquid and the mixed solution is 1:1), and the mixture is reacted at room temperature for 3.5 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material.
[0105] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol, characterized in that: It contains the following steps in order: Step [1] Preparation of 2,5-dibromo-3-aminothiophene product solution and 2,5-dibromo-3-amidethiophene product solution; Step [2] Synthesis of Graphene Oxide / Tungsten Trioxide Nanoparticles, specifically comprising the following operations: b1. Add phosphotungstic acid and cinchoninic acid to ethanol and mix to form an additive solution C; add sodium tungstate, ammonium chloride and graphyne nanoparticles to deionized water and mix to form a base solution C; add a certain amount of additive solution C to the base solution C to form a synthetic solution, put the synthetic solution into a reactor, heat to 60-80°C for reaction for 4-6 hours, and filter to obtain a solid phase graphyne / tungsten trioxide nanoparticle precursor; b2. The obtained solid phase Graphene / tungsten trioxide nanoparticle precursor is placed in a tube furnace and kept at 200 ℃ -250 ℃ for 1 to 2 hours to obtain the Graphene / tungsten trioxide nanoparticles; Step [3] Loading poly 3-amino / 3-amidothiophene and the graphyne / tungsten trioxide nanoparticles on the surface of the nickel foam substrate to finally obtain the nickel foam-based composite material, specifically comprising the following operations: c1. The octacarbonyl dicobalt and the graphyne / tungsten trioxide nanoparticles are added to dimethyl sulfoxide and mixed to form a loading promotion solution; c2. The 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution are mixed in a certain proportion to form a mixed solution, the metal nickel foam is immersed in the mixed solution, and the mixture is immersed at room temperature for 10-30 minutes, and then a certain amount of the loading promotion liquid is added to the mixed solution and fully stirred, and the mixture is reacted at room temperature for 3-4 hours to obtain a nickel foam with poly 3-amino / 3-amidethiophene and graphyne / tungsten trioxide nanoparticles loaded on the surface, which is the nickel foam-based composite material.
2. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Under argon protection conditions, 2,5-dibromo-3-hexylthiophene and hexamethylenediamine were added to ethanol and mixed to form a base solution A; L-proline was added to deionized water and mixed to form an additive solution A; a certain amount of additive solution A was added to the base solution A, and the reaction was carried out at room temperature for 3-5 hours to obtain a 2,5-dibromo-3-aminothiophene product solution; a2. Under argon protection, 2,5-dibromo-3-hexylthiophene and acrylamide were added to ethanol and mixed to form a base solution B; L-pyroglutamic acid was added to deionized water and mixed to form an additive solution B; a certain amount of additive solution B was added to the base solution B, and the reaction was carried out at room temperature for 2-3 hours to obtain a 2,5-dibromo-3-amidethiophene product solution.
3. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 2, characterized in that: In step a1, the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid A is 150-240 mL, and the amount of hexamethylenediamine added is 80-150 g; the concentration of L-proline in the additive liquid A is 90 g / L-130 g / L; and the volume ratio between the additive liquid A and the base liquid A is 1-3:4-7.
4. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 2, characterized in that: In step a2, the amount of 2,5-dibromo-3-hexylthiophene added to each liter of the base liquid B is 130-180 mL, and the amount of acrylamide added is 100-120 g; the concentration of L-pyroglutamic acid in the additive liquid B is 50 g / L-80 g / L; and the volume ratio between the additive liquid B and the base liquid B is 1-2:3-5.
5. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 1, characterized in that: In step b1, the amount of phosphotungstic acid added to the additive liquid C is 200-240 g, and the amount of cinchonine added is 30-50 g per liter; the concentration of sodium tungstate in the base liquid C is 160 g / L-190 g / L, the concentration of ammonium chloride is 50 g / L-90 g / L, and the concentration of graphyne nanoparticles is 230 g / L-250 g / L; the volume ratio between the additive liquid C and the base liquid C in the synthetic liquid is 1-3:3-5.
6. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 1, characterized in that: In step c1, the amount of graphyne / tungsten trioxide nanoparticles added in each liter of the promoting solution is 170-210 g, and the amount of dicobalt octacarbonyl added is 40-70 g.
7. The method for preparing a foamed nickel-based composite material for photocatalytic degradation of p-nitrophenol according to claim 1, characterized in that: In step c2, the volume ratio of the 2,5-dibromo-3-aminothiophene product solution and the 2,5-dibromo-3-amidethiophene product solution in the mixed solution is 1:1; the weight of the nickel foam immersed in each liter of the mixed solution is 130-170 g; The volume ratio between the loading promotion liquid and the mixed liquid is 1:1.
Citation Information
Patent Citations
Composite material, and preparation method and application thereof
CN114085523A
Method for co-producing organic bromide and hydrogen through photocatalysis
CN116836148A